Interview with Paolo Mastrolilli, La Stampa - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass said that the most pressing matter for the G20 is to move quickly together on growth, on vaccines, and on the debt sustainability issues. He highlighted on the need to recognize the connection between sound development policies and sound climate policies. He explained that the debt levels are too high for many countries after Coronavirus (COVID-19) and so, there is a need to see sustainability of debt in order to allow the country's resources to go to education, and to health, and to climate, the things that will build for the future.